A modified nonlinear fatigue damage accumulation model for life prediction of rolling bearing under variable loading conditions. Issue 3 (4th January 2022) - Yu, Aodi; Huang, Hong‐Zhong; Li, Yan‐Feng; Yang, Wenxian; Deng, Zhiming
Abstract: During the use of rolling bearings in wind turbines, aero engines, and other equipment, they often operate under variable operating and loading conditions. The practice has shown that the sequence of these loads and their interaction has a significant impact on the fatigue life of rolling bearings. In order to better understand this issue, a modified nonlinear fatigue damage accumulation model, which considers the influences of both load sequence and load interaction, is proposed in this paper and verified using the fatigue testing data for six materials. Then, the verified model was applied to evaluate the fatigue damage accumulation and fatigue life of a rolling bearing. The results have shown that, compared with the existing models, the proposed model can more accurately predict the damage accumulation and fatigue life of the rolling bearing under variable loading conditions.